Proposed Integrated Marketing Communication (IMC) Strategy for Pura Mangkunegaran as a Cultural Tourism Destination (Pusat Riset dan Inovasi Nasional, 2024)
Pura Mangkunegaran holds a role as a cultural heritage site and one of the primary historical attractions in Surakarta, Central Java. This study examines the strategic challenges faced by the palace as a cultural heritage destination with rising visibility but struggles with strong and meaningful brand understanding. The research adopts a qualitative methodology, collecting data through unstructured in-depth interviews supported by secondary data from the internal management visitor survey. The analysis began with an internal and external assessment using the VRIO and PESTLE frameworks, followed by thematic analysis using Nvivo. This approach ensures a thorough understanding of palace’s strengths, weaknesses, opportunities, and threats (SWOT), which is then synthesized using the TOWS matrix and thematically analyzed to identify key themes leading to the formulation of strategic recommendations using integrated marketing communications (IMC) recommendations. Key findings from the internal analysis indicate that Pura Mangkunegaran possesses several valuable resources but tend to be constrained. The external analysis reveals that the rise of the cultural tourism trend and improved efforts of combining technology show opportunities, while competition with nearby cultural destinations, inconsistent digital communications, and public perception tend to pose challenges. The proposed business strategy using IMC integrates all media mix that Pura Mangkunegaran can utilize to improve visitor experience, specifically in the digital marketing aspect. To support the IMC strategy, the implementation plan for Pura Mangkunegaran combines all initiatives for the 2026 timeline, divided into four quarters. This research contributes to the field of cultural tourism marketing by providing a practical framework that can be applied to increase visit experience and brand understanding.